Analysis Of Internal and External Factors Affecting Oil Palm Farming Productivity in Tebo Regency - Jenida Laoli; Saidin Nainggolan; Yulismi (Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to: describe the characteristics of oil palm farming in Rimbo Ilir District, Tebo Regency; describe the internal and external factors of oil palm farmers in Rimbo Ilir District, Tebo Regency; and analyze the influence of internal factors (number of family dependents, farmers’ ethnicity, farmers’ motivation, and level of cosmopolitanism) and external factors (access to marketing, access to capital, price, and distance) on the productivity of oil palm farming in Rimbo Ilir District, Tebo Regency. The analytical method used is the Partial Least Square (PLS) approach with a total sample of 68 farmers.The results of the study show that: Oil palm farming in the study area is carried out conventionally. Internal factors include the number of family dependents ranging from 1 to 6 persons, with the majority of farmers being of Javanese ethnicity. Farmers in the study area have high motivation and a high level of cosmopolitanism. External factors include access to marketing, where farmers sell their produce to middlemen, loading ramps (RAM), or directly to palm oil mills. The selling price of fresh fruit bunches (FFB) varies, but on average ranges from Rp 2,600 to Rp 3,050 per kilogram, and the distance between plantations and farmers’ residences varies from 0.1 to 8 kilometers. Internal factors have a positive and significant direct effect on productivity. Internal factors also have a positive and significant indirect effect on productivity through the moderating variable of input use.